PENGARUH KUALITAS PRODUK DAN CITRA MEREK (BRAND IMAGE) TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG GALAXY SERIES J (Studi Kasus Pada Konsumen Samsung Galaxy Series J Di Kota Semarang) - Dungo Aryaty Lumban Gaol; Agung Budiatmo (Universitas Diponegoro, 2018)
Product Quality and Brand Image are some factors which can influence of Purchasing Decisionon consumers. So the company is able to offer high quality product and brand image from the consumers needed, it aims to raise a high purchase decision, Samsung Galaxy Series J needs to pay attention to things that affect the Purchase Decision. Problems for market share data Samsung's smartphone in Indonesia continues to decline from 2013-2016 and Samsung's sales in Semarang fluctuate from 2014 to 2016. Every company would expect maximum results from products offered to consumers, namely the amount of production to the product which continues to increase and the sales are also increasing. This type of research is explanatory. Data collection through a questionnaire and interview. The sampling technique using accidental sampling, purposive sampling and area sampling. The sample of this research as many as 100 respondents in Citraland Semarang calculated to analyze data using validity,reability, the coefficient of correlation, simple and multiple regression analysis, the coefficient of determinationand, significance test (t test and F test) with the help of SPSS software version 16.0. The result of research concluded that product quality has a positive and significant influence on partial purchasing decision of 32.7%. Brand imagehas a positive and significant influence on purchasing decision of 36.2%. Through this research indicatesthat product quality and brand image simultaneously have a positive and significant influence on purchasing decision of 41,0, the rest is influenced by another factors. This means thatthe higher product quality and brand image will lead to the higher purchase decisionon Smartphone Samsung Galaxy Series J. Based on the results concludedthat comsumerpreceptions of product quality and brand image is good. Meanwhile, the purchase decisionon Smartphone Samsung Galaxy Series J is high.Suggested to the company to improve product quality andqulity of atteries to fit what consumers need. The company must be able to strengthen the brand image to keep the company’s reputation in a better reputation.